Comparative outcomes of corticosteroids, neuromuscular blocking agents, and inhaled nitric oxide in ARDS: a systematic review and network meta-analysis - Xu, Zhiyuan; Liu, Xiao; Zhang, Liang; Yan, Xianliang (Frontiers in Medicine, 2025)
ObjectivesAcute respiratory distress syndrome (ARDS) is associated with high rates of morbidity and mortality. However, the evidence regarding the effectiveness of commonly used treatments, including corticosteroids, neuromuscular blocking agents (NMBAs), and inhaled nitric oxide (iNO), remains uncertain. Therefore, this study aimed to compare and rank these three treatments to identify the most effective option.Data sourcesWe searched PubMed, Embase, Cochrane Library, and Web of Science for clinical trials from the earliest records to 1 May 2024.Study selection and data extractionClinical trials evaluating three interventions compared with the control group for ARDS were included, with restrictions on any language. Data were extracted by two independent reviewers. Frequentist network meta-analysis (NMA) was performed to identify the most effective intervention, and treatments were ranked using the surface under the cumulative ranking (SUCRA) curve. The primary outcome was 28-day mortality, while secondary outcomes included ventilator-free days up to 28 days, ICU mortality, in-hospital mortality, and the incidence of new infection events.Data synthesisData from 26 clinical trials encompassing 5,071 patients were analyzed. Vecuronium bromide was the most effective strategy for reducing 28-day mortality compared to conventional treatment, iNO, methylprednisolone, and placebo (OR 0.38, 95% CI 0.15–1.00, and OR 0.30, 95% CI 0.10–0.85 and OR 0.25, 95% CI 0.08–0.74 and OR 0.23, 95% CI 0.08–0.65; SUCRA: 96.6%). Dexamethasone was identified as the most effective treatment option for increasing ventilator-free days at 28 days compared to conventional therapy and cisatracurium (MD 3.60, 95% CI 1.77–5.43, and MD 3.40, 95% CI 0.87–5.92; SUCRA: 93.2%). Methylprednisolone demonstrated the highest effectiveness for preventing ICU mortality (SUCRA: 88.5%). Although dexamethasone, cisatracurium, conventional therapy, methylprednisolone, and iNO treatment did not show significant superiority in reducing in-hospital mortality, dexamethasone showed the highest probability of being the most effective treatment option (SUCRA: 79.7%). Furthermore, dexamethasone treatment showed the highest safety in reducing the incidence of new infection events compared with placebo and iNO (OR 0.61, 95% CI 0.42–0.88, and OR 0.33, 95% CI 0.19–0.58; SUCRA: 91.8%).ConclusionThis NMA suggests that corticosteroids may provide benefits to patients with ARDS. While the application of NMBAs may reduce 28-day mortality, iNO did not demonstrate a significant beneficial effect as a therapeutic measure.Systematic review registrationPROSPERO, CRD42022333165 https://www.crd.york.ac.uk/PROSPERO/.